Evaluation of Some Selected Mango Varieties for Fruit Powder Production In Ghana - Edusei, Vida Opoku; Essilfie, Gloria; Saalia, Firibu Kwesi; Ofosu-Anim, John; Eziah, Vincent (Journal of Tropical Crop Science, 2021)
Mango is an important fruit, which receives high patronage in Ghana. However, the highly seasonal and perishable nature of the crop, besides being a constraint to both farmers and processors, also deny consumers the opportunity to enjoy the fruit all year round. Use of the stable powder form of mango can serve to fill the gap during the mango off-season. This study evaluated the fruits of four major mango varieties (“Keitt”, “Kent”, “Palmer” and a local variety) grown in Ghana for their suitability for fruit powder production. The fresh fruit pulp and reconstituted freeze-dried powder of the varieties were analyzed for physicochemical characteristics. The study revealed that “Keitt”, “Kent” and “Palmer”, which are the exotic varieties, had significantly (p≤0.05) high pulp content of 68%, 66% and 63% respectively indicating potential for high fruit powder yield. Acceptable levels of total soluble solids, titratable acidity, ascorbic acid and beta-carotene contents were observed in the fresh fruit and the freeze-dried powders of the varieties. There was no significant (p≤0.05) difference in Yellowness Index between fresh fruit pulp of “Keitt”, “Kent” and “Palmer” and their respective reconstituted freeze-dried powders. These three mango varieties exhibited considerably good quality in terms of physical and chemical characteristics for processing and utilization as fruit powder. The production of high quality mango powder from these varieties could therefore serve as substitutes in the off-season and also reduce postharvest loss.